Factors Affecting the Exercise Capacity in Pediatric Primary Hypertension - Zhang, Hui; Chen, Yeshi; Zheng, Tong; Zhang, Mingming; Li, Xiaohui; Shi, Lin (Frontiers in Pediatrics, 2022)
Purpose: Exercise training is crucial to the early intervention of pediatric primary hypertension (PHT). However, much less is known about exercise capacity in this disease. This work investigated the exercise capacity in pediatric PHT and analyzed the factors affecting exercise capacity. Methods: The study enrolled children with PHT at the Children's Hospital Capital Institute of Pediatrics between July 2017 and July 2020. The Bruce protocol of the treadmill exercise test (TET) was used to assess exercise capacity. Multi-factor ordered logistic regression and generalized linear models were used to analyze factors affecting exercise capacity. Results: Of 190 patients, 146 (76.8%) were male, and the median age was 13 (11, 14). Most children accomplished TET and achieved the submaximal heart rates (189 [99.5%]). Children with lower resting diastolic blood pressure (DBP) and 24h average diastolic blood pressure (ADBP) could achieve a TET stage of 6 or more, whereas children with higher DBP and ADBP could only achieve a TET stage of 3 (P all ＜0.05). Children with lower DBP and 24h ADBP were also associated with greater metabolic equivalents (METs);（r = -0.224, r = -0.152, P all<0.05) . The completion of TET stages was negatively associated with female (OR = 0.174), younger age (OR = 1.908), greater body mass index (BMI) (OR = 0.973), and higher 24h ADBP (OR = 0.981, P all＜0.05). In addition, METs were negatively associated with female (β = -1.854), younger age (β = 0.279), greater BMI (β = -0.123), and higher 24h ADBP (β = -0.063, P all ＜0.05). Conclusions: Exercise capacity was impaired among pediatric PHT patients. Female gender, younger age, greater BMI, and higher 24h ADBP are independently associated with the exercise capacity in pediatric PHT. These findings may help developing scientific exercise prescriptions for pediatric PHT.